CD205-targeted bispecific nanobody enhances antigen presentation and immune responses in FMDV - Li Yang; Xin Sun; Luping Du; Zizheng Cai; Liting Hou; Zhu Qin; Jin Chen; Yu Lu; Xiuli Feng; Ivan Campeotto; Qisheng Zheng; Haiwei Cheng (Veterinary Vaccine, 2025)
Dendritic cells (DCs) are professional antigen-presenting cells (APCs) that play a pivotal role in bridging innate and adaptive immunity, making them a central focus in vaccine development. As a C-type lectin receptor expressed on cDC1 and cDC2 subsets, CD205 facilitates receptor-mediated endocytosis, enabling antigen presentation through both MHC class I and class II pathways, which are critical for activating cytotoxic and helper T cells. In this study, we introduced a CD205-targeted bispecific nanobody (BiNb-CD205/FMDV) as a novel platform for enhancing antigen delivery and immune activation of foot-and-mouth disease virus (FMDV) in pigs. In vitro experiments demonstrated that BiNb-CD205/FMDV could bind efficiently to porcine bone marrow-derived dendritic cells (BMDCs) and show a strong colocalization with acidic organelles such as lysosome, indicating significantly enhancing antigen uptake and effective processing. In vivo immunization results revealed Nb4-Nb205 was effective at enhancing LPB-specific antibody titers, inducing enhanced CD4+ and CD8+ T cell responses. Elevated cytokine levels, including IFN-γ and IL-4 further supported robust immune activation, indicating a balanced Th1/Th2 response. Our results provide preliminary evidence for the feasibility of CD205-targeted bispecific nanobody platforms in enhancing antigen presentation and immune responses. This highlights the potential to expand targeted delivery to the field of animal epidemic diseases and provides a reference for the general application of nanotechnology in viral diseases.